Raman optical activity of tetra-alanine in the poly(l-proline) II type peptide conformation. Issue 3 (3rd January 2017) - Furuta, Masakazu; Fujisawa, Tomotsumi; Urago, Hiroyasu; Eguchi, Takahiro; Shingae, Takahito; Takahashi, Satoshi; Blanch, Ewan W.; Unno, Masashi
Abstract : Raman optical activity spectra of tetra-alanine was characterized by quantum chemical calculations combined with molecular dynamics simulations. Abstract : The poly(l -proline) II (PPII) helix is considered to be a major conformation in disordered polypeptides and unfolded proteins in aqueous solution. The PPII conformation can be identified by using Raman optical activity (ROA), which measures the different intensities of right- and left-circularly polarized Raman scattered light from chiral molecules and provides information on stereochemistry associated with vibrational motions. In the present study, we used tetra-alanine (Ala4 ) as a model system, since its central amide bond adopts the PPII conformation. The predominance of the PPII conformation was supported by 11 ns molecular dynamics (MD) simulations at 300 K. The MD snapshots were used for subsequent quantum mechanical/molecular mechanical (QM/MM) calculations to compute the Raman and ROA spectra. The present MD + QM/MM analysis leads to a good agreement between the observed and simulated spectra, allowing us to assign most of the spectral features including the ROA band near 1320 cm −1, which has been used as a marker for the PPII conformation. This positive ROA band has three components. The lower frequency component near 1310 cm −1 arises from an internal peptide bond, whereas the higher frequency components around 1320–1335 cm −1 appear due to N- and C-terminal peptide groups. The MD + QM/MM calculations also reproduced the electronic circular dichroism spectra of Ala4 . The present results provide a satisfactory framework for future investigations of unfolded/disordered proteins as well as peptides in solutions by chiral spectroscopic methods.